Requirements for Developing Legal Awareness among Students in Iraqi Universities - Amjed Nori Alawadi (International Journal on Humanities and Social Sciences, 2025)
This study aimed to identify the current role of Iraqi universities in developing legal awareness among their students, the obstacles and requirements for this development, and to propose a framework for enhancing legal awareness among students in Iraqi universities. The study employed a descriptive survey methodology. Two questionnaires were used: the first was administered to a stratified random sample of 1,643 male and female students in Iraqi universities, and the second was administered to a stratified random sample of 160 faculty members from Iraqi universities in Dammam. The study yielded several findings, the most important of which are: The study sample of students agreed that the role of Iraqi universities in developing legal awareness among their students is achieved to a moderate degree. The study sample of faculty members agreed that the role of Iraqi universities in developing legal awareness among their students is achieved to a moderate degree. The study sample of faculty members agreed to a moderate degree that there are some obstacles hindering the role of Iraqi universities in developing legal awareness among their students. The study sample of faculty members largely agreed on the need to provide the necessary requirements to activate the role of Iraqi universities in developing legal awareness among their students. There are statistically significant differences between the responses of the study sample of male and female students at the significance level of 0.01 regarding the axis “The reality of the role of Iraqi universities in developing legal awareness for their students” as a whole and the two dimensions (the role of faculty members, and student activities) in favor of female students, while there are no statistically significant differences between male and female students in the two dimensions (the role of university administration, and the courses).